Reformation, Religious Culture and Print in Early Modern Europe
1 online resource
Keywords: Anyone who has studied the history of the Reformation, the book and communication will have come across or been influenced by Andrew Pettegree’s contributions to these fields. The forty-four essays in this Festschrift and its companion volume have been commissioned to cover the broad scope of Pettegree’s areas of interest and expertise, and to reflect and build upon them. The pieces, written by forty-three scholars based at over thirty institutions, are organised around nine key themes, ranging from the intersections of religion and print to the history of book collecting, the periodical press and pioneering book historical research methodologies. This first volume contains nineteen essays. Together with the second volume, 'The Book World of Early Modern Europe: Essays in Honour of Andrew Pettegree, Volume 2' , it offers a wid-ranging survey of the state of current scholarship on religion, printing and media change in early modern Europe. Contributors to this volume: Riccardo Bavaj, Flavia Bruni, Arthur der Weduwen, Alastair Duke, Bruce Gordon, Brian Hanson, Mack Holt, Richard Kirwan, Katell Lavéant, Ian Maclean, Guido Marnef, Jonathan Reid, Alec Ryrie, Grant Tapsell, Margo Todd, Natale Vacalebre, Arjan van Dijk, Malcolm Walsby, and Elise Watson.